Rare complications of anti-melanoma differentiation-associated gene 5 antibody-positive dermatomyositis: Time to nip them in the bud - Yang, Jinming; Yan, Bing (Frontiers in Immunology, 2022)
Anti-melanoma differentiation-associated gene 5 antibody-positive dermatomyositis (MDA5+ DM) is an infrequent autoimmune disease, which mainly distributes in Asians and females. MDA5+ DM usually presents various skin lesions and positive anti-MDA5 antibody (a myositis-specific autoantibody for itself) with amyopathic or hypomyopathic features. For MDA5+ DM patients, rapidly progressive interstitial lung disease is a common complication with a high-speed deterioration and a poor prognosis. Besides, there are other complications of MDA5+ DM patients, including pneumomediastinum, macrophage activation syndrome and spontaneous intramuscular hemorrhage. These complications were rare but lethal, so it is necessary to explore their diagnosis methods, therapies and potential mechanisms, which are helpful for making early diagnoses and timely treatment. To date, several cases and studies have shown distinctive features, diagnoses and treatments of these three rare complications, and there are also some differences among them. In this review, we outlined the characteristics, administration and potential pathogenesis of these rare complications of MDA5+ DM.